Calredoxin represents a novel type of calcium-dependent sensor-responder connected to redox regulation in the chloroplast - Ana Karina Hochmal (Nature Portfolio, 2016)
Calcium and redox signalling have important roles in acclimation processes. Here, the authors characterise a protein from Chlamydomonas reinhardtiithat can integrate calcium and redox-related signalling.